Analysis Of The Influence Of Continuous Training Development And Education On Professional Competence Of Teachers In Public Schools - A. Dara Dewi Mallarangan; Abdul Rahman; Suriani Nur; Zahra Khusnul Lathifah; Fatimah Malini Lubis (Journal on Education, 2024)
The purpose of this study is to determine if teacher professional competence may be increased via education and training. A random lottery was employed to choose a sample of 100 instructors for this study. Data analysis and data visualization are provided through summaries and formulations in numerical form since descriptive statistical methods were used to process the data collected through surveys and document studies. Validity and reliability testing may be used to assess the requirements for the study, and basic linear regression analysis techniques can be used to evaluate the data and generate hypothesis judgments. A correlation value of 0.6 was found based on data processing with the SPSS, and the contribution of variable H0 is rejected as the sig value is less than 0.03, as determined using probability procedures. Thus, it can be inferred from these two approaches that training and education have an impact on raising the professional competence of teachers